The Transformasional Leadership to Increase the Lecturers' Creativity at Higher Education in Indonesia - Adenuddin Alwy, Muhammad; Sari Baso, Rachmie (International Journal of Education and Digital Learning (IJEDL), 2022)
This study aimed to analyze lecturers' perceptions of transformational leadership on lecturers' creativity in independent campus at higher education in Indonesia. The research design used is a quantitative study in which hypotheses are tested through survey methods. The sampling technique in this study was targeted sampling using a non-probability sampling method, and the criteria were lecturers at higher education in Indonesia who had been on the Freedom Campus for > 1 year. Data analysis technique using SEM – PLS (Smart PLS). The findings of this study were that perceptions of transformational leadership had positive effect to lecturers' relationship, however, there was no impact to increase on lecturers' creativity.